Analysis of heat and mass transport characteristics in anode-supported solid oxide fuel cells at various operating conditions. (18th April 2019) - Shen, Qiuwan; Li, Shian; Yang, Guogang; Huang, Naibao; Yuan, Jinliang; Sundén, Bengt
Abstract: In this study, the heat and mass transport characteristics of anode-supported solid oxide fuel cells (SOFCs) are numerically investigated by using a two-dimensional model. The mathematical model is validated by comparing the numerical results with experimental data found in the open literature. The species and temperature distributions of SOFCs at different cell voltages are presented and compared. Effects of operating temperature, flow direction arrangement, and flow velocity on the overall cell performance and local temperature distribution are also analyzed. It is concluded that the local temperature is increased with decreasing operating cell voltage, increasing operating temperature, and decreasing cathode flow velocity. The temperature distribution is significantly changed when counter-flow arrangement is used instead of coflow arrangement. In addition, the effect of anode flow velocity on temperature distribution is negligible.